METODE PENDIDIKAN AKHLAK DALAM KELUARGA MUSLIM DI DESA TRIHARJO KECAMATAN MERBAU MATARAM KABUPATEN LAMPUNG SELATAN - Yuyun Khotimah; Zulhanan Zulhanan; Umi Hijriyah; Muhammad Akmansyah (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2021)
Abstract: This study aims to determine the application of moral education methods in Muslim families in Triharjo village Merbau Mataram South Lampung district. This research uses descriptive qualitative research. Data collection techniques in this study were through observation, interviews and documentation, then data analysis was carried out by means of data reduction, data presentation and drawing conclusions, then testing the validity of the data using triangulation techniques. The results showed that the application of the moral education method in Muslim families in Triharjo village was going well. In applying the habituation method, parents have accustomed their children to worship and behave well. The application of exemplary methods and advice has also been applied well, but in the application of the method of attention / supervision of parents in Triharjo village, it has not been able to apply it optimally because of parents' busy work which causes parents to have less time to supervise their children, but with facilities. and the existing program in Triharjo village can be an alternative for parents in building children's morals when they are busy working. In terms of giving punishment and gifts, each parent in Triharjo village has his own way, but the parents of Triharjo village as much as possible avoid physical punishment in terms of giving punishment to children. Keywords: Methods, Moral Education, Family